The Influence of Bintang Aquarium Store's Brand Image on Consumer Purchasing Decisions During the Covid-19 Pandemic - Pieter Haryanto; Kristyana Dananti (ProBisnis : Jurnal Manajemen, 2023)
This study aims to analyze the effect of brand image, consisting of company image, product image, and consumer image variables, on consumer purchasing decisions. The sample in this study consisted of 40 respondents who were willing to take the time to fill out the questionnaire, taken using purposive and convenience sampling methods. Data collection was carried out using questionnaires. Data analysis was performed using multiple linear regression tests with SPSS 17.00 software. The results of this study indicate that the company image has a significant effect on purchasing decisions at Bintang Aquarium Solo Store, as evidenced by a significance value of 0.002 and a t-count of 2.012, while the t-table is 1.985, then the t-count value is greater than the t-table value. The product image has a significant effect on purchasing decisions at Bintang Aquarium Solo Store, as evidenced by a significance value of 0.000 and a t-count of 2.900, while the t-table is 1.985, then the t-count value is greater than the t-table value. Consumer image has a significant effect on consumer purchasing decisions at Bintang Aquarium Solo Store, as evidenced by a significance value of 0.001 and a t-count of 2.027, while the t-table value is 1.985, then the t-count value is greater than the t-table value.